Hierarchically Porous N‐Doped Carbon Fibers as a Free‐Standing Anode for High‐Capacity Potassium‐Based Dual‐Ion Battery. Issue 37 (20th August 2019) - Zhang, Meng; Shoaib, Muhammad; Fei, Huilong; Wang, Tao; Zhong, Jiang; Fan, Ling; Wang, Lei; Luo, Haiyan; Tan, Shan; Wang, Yaya; Zhu, Jian; Hu, Jiawen; et al.
Abstract: Potassium‐based dual‐ion batteries (KDIBs) have emerged as a new generation of rechargeable batteries, due to their high cell voltage, low cost, and the natural abundance of potassium resources. However, the low capacity and poor cycling stability largely hinder the further development of KDIBs. Herein, the fabrication of hierarchically porous N‐doped carbon fibers (HPNCFs) as a free‐standing anode for high‐performance KDIBs is reported. With a free‐standing hierarchical structure (micro/meso/macropores and nanochannels) and high‐content of nitrogen doping, the HPNCFs not only provide intrinsic electron pathways and efficient ion transport channels, but also afford sufficient free space to tolerate the volume change during cycling. Consequently, the KDIBs made from a graphite cathode and an optimized HPNCFs anode deliver a high reversible capacity of 197 mAh g −1 at a specific current of 50 mA g −1, and excellent cycling stability (65 mAh g −1 after 346 cycles at a specific current of 100 mA g −1, the capacity calculation of the KDIBs is based on the mass of the anode). These results indicate that the properly designed HPNCFs can effectively improve the capacity and cycling stability of the KDIBs, indicating a great potential for applications in the field of high‐performance energy‐storage devices. Abstract : A potassium‐based dual‐ion batteries (KDIBs) are made from a hierarchically porous N‐doped carbon fibers (HPNCFs) anode and a graphite cathode. During the charging process, the anions (PF6 − ) intercalates into the graphite cathode, while the cations (K + ) intercalate into the HPNCFs anode. During the discharge process, anions and cations de‐intercalate from the corresponding electrode, returning to the electrolyte. The KDIBs manifest high working voltage and high reversible capacity.